Penerapan Activity Based Costing (ABC) System Dalam Penghitungan Profitabilitas Produk - Riki Martusa; Yoanes Dicky (Jurnal Akuntansi, 2011)
PT "X" is one of the companies working in the field of footwear products in the form in which women work shoes and slippers women marketed in the domestic market. PT "X" has not made an accurate calculation of production costs due to the method of calculating the current cost of production is traditional to perform equalization of resources regardless of the cost of the percentage of resource usage for each product. Application of the method of Activity Based Costing (ABC) System in calculating the production cost of a product can improve the system of calculating production costs that are currently carried out by PT "X". The results of calculating the cost of production using the method of Activity Based Costing (ABC) System can be used in calculating the profitability of a product that can be used by PT "X" to set the appropriate selling price by taking into account production costs and profitability of its products, so that the PT "X" can compete in this tight business world.Keywords: Activity Based Costing (ABC) System and Product Profitability.